2023
DOI: 10.1002/ptr.7928
|View full text |Cite|
|
Sign up to set email alerts
|

Scutellarein alleviates chronic obstructive pulmonary disease through inhibition of ferroptosis by chelating iron and interacting with arachidonate 15‐lipoxygenase

Abstract: Ferroptosis, an iron‐dependent cell death characterized by lethal lipid peroxidation, is involved in chronic obstructive pulmonary disease (COPD) pathogenesis. Therefore, ferroptosis inhibition represents an attractive strategy for COPD therapy. Herein, we identified natural flavonoid scutellarein as a potent ferroptosis inhibitor for the first time, and characterized its underlying mechanisms for inhibition of ferroptosis and COPD. In vitro, the anti‐ferroptotic activity of scutellarein was investigated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Liu et al found that scutellarin prevented RSL3-induced ferroptosis and damage in BEAS-2B cells and alleviated LPS/CS-induced COPD in mice. Mechanistically, scutellarein directly chelates Fe 2+ and interacts with ALOX15 to reduce lipid peroxidation, reverse GPX4 downregulation, and block Nrf2/HO-1 and JNK/ p38 pathway overactivation [169]. According to existing research, the main effect of this intervention is the suppression of ferroptosis, leading to enhanced mitigation of chronic inflammation and airway constriction in individuals with COPD.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Liu et al found that scutellarin prevented RSL3-induced ferroptosis and damage in BEAS-2B cells and alleviated LPS/CS-induced COPD in mice. Mechanistically, scutellarein directly chelates Fe 2+ and interacts with ALOX15 to reduce lipid peroxidation, reverse GPX4 downregulation, and block Nrf2/HO-1 and JNK/ p38 pathway overactivation [169]. According to existing research, the main effect of this intervention is the suppression of ferroptosis, leading to enhanced mitigation of chronic inflammation and airway constriction in individuals with COPD.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…These observations, consistent with our in vitro experimental outcomes, strongly suggest the therapeutic potential of Scu in the treatment of OA. After consulting other studies, we determined that 20 mg/kg was the ideal Scu dosage, upon which we better observed the effect of Scu on OA (Liu et al, 2021;Liu, Zhang, et al, 2023). Given the significance of the PI3K/ Akt pathway in OA, we consider the discovery of novel inhibitors of this pathway as targeted medicines to be promising.…”
Section: Network Pharmacology Analysis Suggests Scu May Function Via ...mentioning
confidence: 99%
“…Cell death processes such as apoptosis, necrosis, ferroptosis, and pyroptosis are believed to be associated with the progression of COPD. [7][8][9][10] These processes typically interact within a complex network, contributing to the sustained inflammatory state observed in COPD patients. A comprehensive understanding of the specific roles of these cell death pathways and how they interplay in the pathophysiology of COPD is crucial for comprehension of this disease.…”
Section: Introductionmentioning
confidence: 99%